"Cunning of Reason" and the Igbo concept of Chi: Towards a philosophical rapprochement with Hegel. Issue 1 (2nd January 2021) - Ude, Donald Mark C
Abstract : The central argument of this article is that there is a remarkable conceptual parallel between Hegel's famous notion of the "cunning of Reason" and the philosophically profound concept of Chi in Igbo metaphysics. By way of establishing this parallel, the article advances the following subsidiary but complementary points: Chi is also "cunning" in its dynamics; both principles (i.e. Chi and Reason/Spirit) are non-deterministic because they try to maintain a dialectic balance between destiny and individual responsibility; both possess divine attributes; and community serves as an invaluable medium of operation for both. The scholarly significance of the article lies in its attempt not only to systematise the Igbo thought on Chi by eliminating the vestiges of discredited "ethno-philosophy", but also to open up a constructive dialogue between Hegel and elements of African philosophy, using Igbo metaphysics as a placeholder. This is against the backdrop of certain discontents generated by Hegel's famous uncomplimentary and racist remarks on Africa. Seen in this light, the article may well be an exercise in "rapprochement".